(untitled) (Polifonia, 1994)
ABSTRACT: This paper examines the teaching of language, specificaly, the language aquisition process of writing from the experimentalist and vanguard viewpoint of the "concrete poets" (poets who work directly with sounds of words and the form of the poem). It contrasts the referencial and metalinguistic functions, which are predominant in school, to the poetic functions of language.